2021
DOI: 10.1101/2021.11.30.470608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ChiMera: An easy to use pipeline for Bacterial Genome Based Metabolic Network Reconstruction, Evaluation and Visualization

Abstract: Several genome scale metabolic reconstruction tools have been developed in the last decades. They have helped to construct many metabolic models, which have contributed to a variety of fields, e.g., genetic engineering, drug discovery, prediction of phenotypes, and other model-driven discoveries. However, the use of these programs requires a higher level of bioinformatic skills, and most of them are not scalable for multiple genomes. Moreover, the functionalities required to build models are generally scattere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The procedure has been detailed in Methods section. Briefly, we first performed protein annotations on the genome assemblies of all strains using Bakta (v1.4.0) (43), the annotations were then used to build draft metabolic networks using Chimera pipeline (44). Finally, KEGG pathway information was extracted from files containing the genome-wide metabolic mapping information (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure has been detailed in Methods section. Briefly, we first performed protein annotations on the genome assemblies of all strains using Bakta (v1.4.0) (43), the annotations were then used to build draft metabolic networks using Chimera pipeline (44). Finally, KEGG pathway information was extracted from files containing the genome-wide metabolic mapping information (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic pathway enrichment analysis The genome sequences were first subjected to annotation using Bakta pipeline (v1.4.0) [41]. Strain-specific genome-scale metabolic models were generated from the Bakta protein annotations using CarveMe algorithm (v1.4.1) [54] part of Chimera pipeline [42]. KEGG [46] pathway information for each strain was retrieved from Chimera outputs and merged to generate pathway enrichment heatmaps.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-scale metabolic network reconstructions (GENREs) are a mathematical framework encompassing much of the known metabolic information on an organism (13). A draft GENRE can be generated with an annotated genome and several automated network reconstruction tools (14)(15)(16)(17), then extensively manually curated using published literature and experimental data. GENREs can simulate all possible growth capabilities of an organism, which are then constrained by biological and physical parameters such as metabolite availability and optimized for a desired outcome, such as biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…This tool combines model creation, gap-filling, flux balance analysis (FBA), and metabolic network visualization to create a simulation-ready genomescale model, based on CarveMe (17), COBRApy (22), Escher (23), and PSAMM (24) algorithms. All the steps are done automatically for the user, reducing the need for bioinformatics skills (25).…”
Section: Chimeramentioning
confidence: 99%
“…The prediction capabilities of ChiMera models were also compared with manually curated models. Both sets of models were simulated using 46, 50, and 70 different carbon sources for B. subtilis (27,28), E. coli (23,24), and P. putida models (25), respectively (Supplementary Table 4, 5 and 6). This analysis suggested that ChiMera models were able to perform comparably to manually-curated models.…”
Section: Comparison With Manually Curated Modelsmentioning
confidence: 99%